Evaluating Social and Functional Effectiveness of Community Agroparks: A Multidimensional Approach from Malang City - Hasan, Khojanah; Rizky, Nina; Afrilia, Nur Khusmiyah (PANGRIPTA, 2025)
Community agroparks represent an innovative approach to urban green space management, combining ecological services, social interaction, aesthetic value, and local economic participation. This study adopts a multidimensional analytical approach to evaluate their effectiveness in Malang City, Indonesia. Using Multidimensional Scaling (MDS), agroparks were classified into four typologies based on facility provision, green coverage, and community activity levels. A Service Quality Gap Analysis was then applied to assess perceived performance across ecological, socio-cultural, aesthetic, and economic dimensions. Findings reveal that community-managed agroparks outperform government-managed ones in socio-cultural engagement, but still face gaps in aesthetic quality and income- generating potential. The study contributes to urban sustainability research by operationalizing a combined typology–gap framework to measure agropark performance and offering targeted recommendations to improve infrastructure design, participatory programming, and local economic integration. These insights support policy directions aimed at enhancing the multifunctionality of agroparks and advancing SDG 11 (Sustainable Cities and Communities).